Feedback and metal enrichment in cosmological smoothed particle hydrodynamics simulations - I. A model for chemical enrichment - Scannapieco, Cecilia (2005)
We discuss a model for treating chemical enrichment by Type II and Type Ia supernova (SNII and SNIa) explosions in simulations of cosmological structure formation. Our model includes metal-dependent radiative cooling and star formation in dense collapsed gas clumps. Metals are returned into the diffuse interstellar medium by star particles using a local smoothed particle hydrodynamics (SPH) smoothing kernel. A variety of chemical abundance patterns in enriched gas arise in our treatment owing to the different yields and lifetimes of SNII and SNIa progenitor stars. In the case of SNII chemical production, we adopt metal-dependent yields. Because of the sensitive dependence of cooling rates on metallicity, enrichment of galactic haloes with metals can in principle significantly alter subsequent gas infall and the build-up of the stellar components. Indeed, in simulations of isolated galaxies we find that a consistent treatment of metal-dependent cooling produces 25 per cent more stars outside the central region than simulations with a primordial cooling function. In the highly enriched central regions, the evolution of baryons is however not affected by metal cooling, because here the gas is always dense enough to cool. A similar situation is found in cosmological simulations because we include no strong feedback processes which could spread metals over large distances and mix them into unenriched diffuse gas. We demonstrate this explicitly with test simulations which adopt suprasolar cooling functions leading to large changes both in the stellar mass and in the metal distributions. We also find that the impact of metallicity on the star formation histories of galaxies may depend on their particular evolutionary history. Our results hence emphasize the importance of feedback processes for interpreting the cosmic metal enrichment.